Thinking Skills Don’t Protect Service Workers from Replacement by Artificial Intelligence - Vorobeva, Darina (2022)
Vorobeva, D., El Fassi, Y., Costa Pinto, D., Hildebrand, D., Herter, M. M., & Mattila, A. S. (2022). Thinking Skills Don’t Protect Service Workers from Replacement by Artificial Intelligence. Journal of Service Research, 25(4), 601-613. https://doi.org/10.1177/10946705221104312----- Funding: The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This work was supported by the Foundation of Science and Technology (FCT Portugal) [DSAIPA/DS/0113/2019]. ---%ABS4%